Identifying and validating the dimensions and components of improving the medical education system in the implementation of online curricula - Gita Zandieh; Aladdin Etemad Ahri; Zolfaghar Rashidi (Social Determinants of Health)
Background: The current research was conducted with the aim of identifying and validating the dimensions and components of online curriculum implementation.